PREVALENCE OF FALLS IN HYPERTENSIVE AND DIABETIC ELDERLY (CIPEEX, 2025)
The analysis of the presence of hypertension and diabetes and falls in the elderly seeks to determine arelationship between these variables, aiming to develop and advance prevention and awarenessmechanisms regarding this problem that persists in the lives of the elderly. The objective of this studywas to determine the prevalence of falls among community-dwelling elderly individuals who havehypertension and diabetes mellitus. The study consists of a data snapshot, in a descriptive andquantitative cross-sectional manner, where economic and sociodemographic aspects, general health,level of frailty, and functional autonomy of the elderly were evaluated. Elderly individuals aged 60 orolder, with hypertension and diabetes mellitus, were included in the study. The sample consisted of onehundred and ten elderly individuals (n = 110) who met the inclusion criteria and agreed to participate. Itwas found that 38.2% (n=42) of the elderly with hypertension and diabetes mellitus had falls in the lasttwelve months, and 21.8% (n=24) reported having had only one fall in the last twelve months. Theresults also indicate that 36.84% of the elderly with diabetes mellitus and 50% of the elderly withhypertension reported having fallen in the last 12 months, demonstrating a considerable prevalence ofthese occurrences in this group. Although preventive actions have reduced the number of falls, it isimportant to continue focusing on strategies to further decrease this prevalence and improve the qualityof life for the elderly.
Keywords: Elderly health; hypertension; diabetes mellitus; falls